Evaluation of Different Wheat Establishment Methods at Agricultural Machinery Testing and Research Centre, Nawalpur, Sarlahi, Nepal - Jha, Ram Nath; Ansari, Md. Shamshad; Thakur, Manish (International Journal of Bio-resource and Stress Management, 2019)
The labour scarcity has been the serious problem in Nepalese agriculture due to youth migration in urban areas and in gulf countries in search of better opportunities. Lack of human resources in agriculture has compelled farmers to find out alternate choice. Mechanization in wheat farming is one of the best solutions to overcome scarce labor for better production. In order to address this issue, an experiment on uses of different agricultural machineries and cultivation practices in wheat crop was conducted at AMTRC during 2017-18 and 2018-19. Experiments were carried out in three replications with six treatments in 2800 m2 plot size. The wheat variety Gautam was sown at the rate of 120 kg ha-1 and other cultural practices were followed as per recommendation. The pooled analysis of two years data of grain yield was significant at 1% level. The highest yield of 3659.17 kg ha-1 was obtained in treatment where zero-till seed-drill (ZTSD) machine was used for wheat cultivation followed by the treatment where power tiller operated seed-drill (3547.50 kg ha-1) was used. The lowest mean grain yield (3005.00 kg ha-1) was recorded in treatment-3 for which seed sowing rotavator was used in experiment. The average gross margin of two years was obtained highest (Rs. 67767.51 ha-1) by treatment-5, the Zero Till Seed Drill (ZTSD) machine. In this treatment the total variable cost was 18.29% less than farmers’ practices. Similarly the gross margin was also 16.66 % and yield was more than 10% higher than farmer’s practices (Check) obtained in ZTSD machine used treatment.